Analisis Desain Kantor Post-Pandemi Covid-19 di DKI Jakarta - Surya Gunanta Tarigan; Khalid Abdul Mannan (Universitas Udayana, 2022)
Pandemic Covid-19 has reshaped the way we work and how we define the workplace which before the pandemic had been strongly associated with the office. During the pandemic, almost all companies implemented ‘work from home (WFH)’ which ultimately force each company to redefine the importance of ‘office.’ The shift from physical space to virtual space makes work flexibility even greater. In addition, paperless work allows tasks to be done anywhere. The implication of this transformation is that the office most likely will adapt to rapidly evolving new functions. The office function, which before pandemic Covid-19 was a place for collaboration among clients, employees, and vendors, can now be facilitated with digital platforms. This study analyzes the office future and how office design adapts to changing needs of the post-pandemic Covid-19 workplace. The research is conducted using an exploratory qualitative method where interviews were conducted with professionals from architectural and interior design bureaus practicing across DKI Jakarta. This study finds that it is that in the future, an ‘office’ will be seen more as a place to build corporate culture, to conduct training, as a social place for employees, and a place to meet clients and attract potential talents. It also discusses the possibility to implement the concept of a ‘hybrid office’ as a solution in the future. Keywords: office design; workplace; Jakarta; pandemic Covid-19 AbstrakSalah satu dampak pandemi Covid-19 adalah mengubah cara kita bekerja dan bagaimana kita mendefinisikan ‘tempat kerja‘ yang selama ini identik dengan kantor. Selama masa pandemi hampir semua perusahaan menerapkan work from home (WFH) yang pada akhirnya membuat perusahaan harus mendefinisikan kembali arti penting kantor bagi perusahaan. Implikasi dari masalah ini adalah kantor harus bisa beradaptasi terhadap fungsi baru yang kemungkinan besar akan berubah. Tujuan penelitian yaitu menganalisa perubahan kantor sebagai tempat bekerja dan bagaimana desain kantor beradaptasi dengan perubahan kebutuhan akan tempat kerja post-pandemi Covid-19. Penelitian dilakukan dengan metode kualitatif eksploratif dimana interview dilakukan dengan profesional dari biro arsitektur maupun interior yang merancang perkantoran di DKI Jakarta. Kemungkinan kantor kedepannya lebih dipandang sebagai tempat membangun budaya perusahaan, tempat melakukan pelatihan dan training, tempat bersosialisasi karyawan serta menjamu klien dan mengundang talent potensial. Study ini juga mendiskusikan bagaimana konsep kantor hybrid dapat menjadi solusi ke depannya.Kata kunci: desain kantor; ruang kerja; Jakarta; pandemi Covid-19